2022
DOI: 10.22441/jurnal_mix.2022.v12i3.005
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Quadruple Helix Collaboration and Quintuple Helix Innovation as Solutions for Post Covid 19 Economic Recovery

Abstract: The COVID-19 pandemic has had a serious impact on the health, economy, transportation, and other industrial crises. The implementation of the lockdown or PSBB has disrupted the operations of various economic sectors.Objectives: The purpose of this research is to describe the concept of the Quadruple Helix collaboration and the Quintuple Helix Innovation model as part of the collaboration, innovation, and synergy initiatives between multi actors to help find solutions in an effort to recover the national econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…This statement is in harmony with the old tradition that accompanied the journey and development of cooperatives formed into associations of people on the basis of equality of degrees of human nature, regardless of direction, religion, politics, voluntarily entering into membership in it (Paranesa et al, 2019). Sustainable adaptive and innovative cooperation that synergizes well between the parties involved from multirole actors is the key to success towards long-term orientation goals Wahdiniwaty et al, 2022). The togetherness of members is the foundation for the development and progress of cooperatives whose activities are based on cooperative principles; togetherness, and for members, as well as a people's economic movement based on family principles.…”
Section: Article Informationsupporting
confidence: 64%
“…This statement is in harmony with the old tradition that accompanied the journey and development of cooperatives formed into associations of people on the basis of equality of degrees of human nature, regardless of direction, religion, politics, voluntarily entering into membership in it (Paranesa et al, 2019). Sustainable adaptive and innovative cooperation that synergizes well between the parties involved from multirole actors is the key to success towards long-term orientation goals Wahdiniwaty et al, 2022). The togetherness of members is the foundation for the development and progress of cooperatives whose activities are based on cooperative principles; togetherness, and for members, as well as a people's economic movement based on family principles.…”
Section: Article Informationsupporting
confidence: 64%
“…Pernyataan ini, sesuai dengan perjalanan dan perkembangan koperasi yang dibentuk menjadi perkumpulan orang-orang atas dasar persamaan derajat kodrat manusia, dengan tidak memandang haluan, agama, politik, secara sukarela masuk menjadi anggota di dalamnya (Paranesa et al, 2019). Kerjasama adaptif dan inovatif berkelanjutan yang bersinergi dengan baik antara pihak-pihak yang terlibat dari para aktor multiperan menjadi kunci keberhasilan menuju tujuan orientasi jangka panjang Wahdiniwaty et al, 2022). Kebersamaan anggota menjadi tumpuan perkembangan dan kemajuan koperasi yang kegiatannya berlandaskan prinsip-prinsip koperasi; kebersamaan, dan untuk anggota, juga sebagai gerakan ekonomi rakyat yang berlandaskan azas kekeluargaan.…”
Section: Pendahuluanunclassified
“…This model is inspired and adopts the involvement of helix roles framed in synergy and continuous innovative collaboration in finding solutions, solving problems and achieving goals done together. For example, what Saepuloh et al, (2022), did, suggested a solution to national economic recovery after COVID-19 by involving four actors (quadruple helix); Wahdiniwaty et al, (2022), considering the involvement of five helixes (quintuple helix) in efforts to find solutions to national economic recovery after COVID-19;, who consider the role of the six helix (hexa helix) as a model of collaboration, innovation and multi-actor synergy initiatives to help find solutions to national economic recovery after COVID-19 in implementing government policies. The social element in learning and being close to society Bandura (1977), in the study of , seems to be relevant for individuals and society, because it is very suitable for their learning habits in the social environment, their behavior and activities.…”
Section: Introductionmentioning
confidence: 99%